Clinical experience of reoperative right ventricular outflow tract reconstruction with valved conduits: risk factors for conduit failure in long-term follow-up - Havova, Mariia; Gebauer, Roman; Antonova, Petra; Spatenka, Jaroslav; Burkert, Jan; Fabian, Ondrej; Modrak, Martin; Rohn, Vilem (Cell and tissue banking, 2024)
Reconstruction of right ventricular outflow tract in patients with congenital heart disease in various age groups remains a controversial issue. Currently, a little is known about the fate of secondary and subsequent conduit. The aim of the study was to determine risk factors of conduit failure, evaluate long-term conduit survival, find out which type of conduit should be preferred in case of reoperations. We performed a retrospective analysis of a total of 249 records of valved conduit secondary and subsequent replacement in right ventricular outflow tract in 197 patients. Median follow-up was 5.7 years. The study endpoints were defined as conduit explants; balloon dilatation of the graft (excluding balloon dilatation of left/right pulmonary artery), transcatheter pulmonary valve implantation; heart transplantation or death of the patient. There were total of 21 deaths (11% mortality) among 197 patients during the follow-up, 2 patients underwent heart transplant, in 23 implanted conduits pulmonary angioplasty or/including transcatheter pulmonary valve implantation was afterwards performed due to graft failure, conduit had to be explanted in 46 cases. After 28 years follow-up, freedom from graft failure after 5 years was 77%, 48% after 10 years and 21% after 15 years. Reoperative right ventricular outflow tract reconstruction demonstrates good mid-term and acceptable long-term outcomes regardless of the type of conduit implanted. Worse long-term graft survival of secondary and further conduits is associated with younger age of the recipient at implantation, small size of the conduit, younger age of donor and male donor in case of allograft implantation.
Keywords: výsledek terapie; srdeční komory; Male; Xenograft; retrospektivní studie; Risk Factors; Conduit failure; Right ventricular outflow tract; následné studie; Infant; vrozené srdeční vady; Valved conduit; mužské pohlaví; Allograft; Follow-Up Studies; Treatment Outcome; lidé; Humans; kojenec; rizikové faktory; Heart Defects, Congenital; Heart Ventricles; Reoperation; Retrospective Studies; reoperace